PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMUNIKASI SEBAGAI VARIABEL INTERVENING PADA KANTOR PIMPINAN PUSAT MUHAMMADIYAH JAKARTA - Jowanda Harahap; Imam Muhtadin; Hanifa Syavina (Taksasila Edukasi Insani, 2025)
This study explores how transformational leadership and work motivation influence employee performance through the mediating role of communication within the Central Board of Muhammadiyah in Jakarta. Rather than merely serving as a tool for information transfer, communication emerges as a vital bridge that connects leadership practices and personal motivation to tangible work outcomes. The findings reveal that when leaders inspire and empower their teams, and when employees are driven by both personal and spiritual commitment, communication becomes more open, meaningful, and effective. In turn, this strengthens collaboration, enhances mutual understanding, and ultimately improves performance. In the context of a large religious and nonprofit organization like Muhammadiyah, where service is deeply tied to faith and collective responsibility, effective communication is not just administrative—it is relational and value-driven. This suggests that sustainable organizational success depends not only on strong leadership or individual motivation, but on how well these forces are expressed, shared, and lived through everyday dialogue. Building trust, encouraging participation, and fostering two-way communication should therefore be central to leadership and human resource strategies in similar institutional settings. Keywords: Transformational Leadership, Work Motivation, Communication, Employee Performance